2016
DOI: 10.1371/journal.pone.0152658
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia during Carotid Endarterectomy: A Safety Study

Abstract: BackgroundCEA is associated with peri-operative risk of brain ischemia, due both to emboli production caused by manipulation of the plaque and to potentially noxious reduction of cerebral blood flow by carotid clamping. Mild hypothermia (34–35°C) is probably the most effective approach to protect brain from ischemic insult. It is therefore a substantial hypothesis that hypothermia lowers the risk of ischemic brain damage potentially associated with CEA. Purpose of the study is to test whether systemic endovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…In this study, there were no significant differences in the perioperative blood loss and blood transfusion ratio between the two groups. This is inconsistent with the conclusions by Candela et al (2016). The possible reason was that routine warming measures were taken by both groups of patients, there was no severe hypothermia in the two groups, and all patients underwent laparoscopic minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 63%
“…In this study, there were no significant differences in the perioperative blood loss and blood transfusion ratio between the two groups. This is inconsistent with the conclusions by Candela et al (2016). The possible reason was that routine warming measures were taken by both groups of patients, there was no severe hypothermia in the two groups, and all patients underwent laparoscopic minimally invasive surgery.…”
Section: Discussionmentioning
confidence: 63%
“…A lower metabolic rate will progressively improve global neurological outcomes and reperfusion injury (34). Early cooling has been used in a phase II trial with stroke patients to establish its safety and feasibility (35). Induced therapeutic hypothermia for 1 to 3 days has shown to be effective in dense stroke patients treated without neuro-vascular intervention (15,30,31).…”
Section: Targeted Hypothermiamentioning
confidence: 99%
“…Animal studies have previously shown reduced brain oxidative stress when regulated hypothermia is applied during hypoxic ischemia (6).It seems reasonable to assume the same protective effect during carotid clamping. Moderate hypothermia has been suggested to be feasible and safe during CEA in a small previous study (7).…”
Section: Introductionmentioning
confidence: 96%
“…Moderate hypothermia has been suggested to be feasible and safe during CEA in a small previous study. 7 …”
mentioning
confidence: 99%